Does everyone have a price? Understanding people's attitude towards online and offline price discrimination - Joost Poort; Frederik J. Zuiderveen Borgesius (Internet Policy Review, 2019)
Online stores can present a different price to each customer. Such algorithmic personalised pricing can lead to advanced forms of price discrimination based on the characteristics and behaviour of individual consumers. We conducted two consumer surveys among a representative sample of the Dutch population (N=1233 and N=1202), to analyse consumer attitudes towards a list of examples of price discrimination and dynamic pricing. A vast majority finds online price discrimination unfair and unacceptable, and thinks it should be banned. However, some pricing strategies that have been used by companies for decades are almost equally unpopular. We analyse the results to better understand why people dislike many types of price discrimination.
Keywords: 300; Price discrimination; Personalised pricing; Dynamic pricing; Algorithmic pricing; Data protection; Data protection law